2018
DOI: 10.18805/lr-3986
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur management in groundnut for higher productivity and profitability under Semi-Arid condition of Rajasthan, India

Abstract: The present study was planned to evaluate the performance of groundnut (Arachis hypogaea L.) under varying levels of sulphur and its sources under Semi-Arid condition of Rajasthan. Application of 60 kg S/ha resulted 8.8, 23.8 and 59.6% more pod/plant than 45, 30 and 15 kg S/ha, respectively. Gypsum as a source of S recorded 15.4 and 50.4% higher pods/ plant over SSP and elemental sulphur, respectively. However, number of kernels/pod increased significantly upto 45 kg/ha only. Gypsum and SSP improved the kernel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
2
7
0
Order By: Relevance
“…Since sulphur is an integral part of oil, the increased availability of sulphur might have favorably influenced the synthesis of essential metabolism for higher oil content. Similar results were reported by Jat and ahlawat [24] and Yadav [25].…”
Section: Nutrient Uptake By Whole Plant Vs Yield and Quality Attributessupporting
confidence: 92%
“…Since sulphur is an integral part of oil, the increased availability of sulphur might have favorably influenced the synthesis of essential metabolism for higher oil content. Similar results were reported by Jat and ahlawat [24] and Yadav [25].…”
Section: Nutrient Uptake By Whole Plant Vs Yield and Quality Attributessupporting
confidence: 92%
“…Groundnut is an important kharif crop grown by the farmers of Bikaner in Rajasthan (Yadav et al, 2019). Though, groundnut occupies important position in the district, still a vast yield gap exists between potential yield (9 t ha -1 ) and the yield obtained (1 t ha -1 ) under real farming situation (Johansen and Nageswara Rao, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…soil loosening, and S regulated the amino acid synthesis and protein formation, which indirectly helped in regulating the plant metabolism and growth of plants (Anthati 2011). The increase in pod yield was mainly ascribed to improvement in yield attributes with S application in addition to its multiple roles in metabolism as an essential constituent of amino acids and also improvement in vegetative structure, production of reproductive structures and assimilates, thereby maintaining balanced source-sink relationship (Yadav et al 2019). The supply of Si through SBG also improved the pod yield.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the positive effect of Si on protein content in rice (Ahmad et al 2013), soybean (Shwethakumari andPrakash 2018) andwheat (Gong et al 2005) has also been reported. The increase in oil content and yield with SBG application was mainly due to supply of S by SBG as it is required for the synthesis of chlorophyll, S-containing amino acid and oil synthesis (Yadav et al 2019). Groundnut is an oil and protein-rich crop, and there is a mutual relationship between oil and protein productions, which means that protein components are produced first and then the plant uses these substances for oil synthesis (Gashti et al 2012).…”
Section: Discussionmentioning
confidence: 99%